90.7k views
4 votes
What is the solution of √x-5 = x-11

User ArunPratap
by
5.1k points

1 Answer

1 vote
Hey!


To solve x in this equation we must first add five to both sides to get
√(x) on its own.

Original Equation :

√(x) - 5 = x - 11

New Equation {Added 5 to Both Sides} :

√(x) =x-6

Now we must square both sides of the equation.

Old Equation :

√(x) =x-6

New Equation {Changed by Squaring Both Sides} :

x= x^(2) -12x+36

And now we must solve the new equation.

Step 1 - Switch sides

x^(2) -12x+36=x

Step 2 - Subtract x from both sides

x^(2) -12x+36-x=x-x

Step 3 - Simplify

x^(2) -13x+36=0

Now we need to solve the rest of the equation using the quadratic formula.


\frac{-(-13)+ \sqrt{(-13) ^(2)-4*1*36 } }{2*1}


{13+ \sqrt{(-13)^(2)-4*1*36 }=13+ √(25)


(13+ √(25))/(2)


√(25)=5


(13+5)/(2)


(18)/(2)

9


\frac{-(-13)- \sqrt{(-13) ^(2) -4*1*36} }{2*1}

4

So, this means that in the equation
√(x) -5=x-11,
x = 9 and x = 4.

Hope this helps!


- Lindsey Frazier ♥
User GuRAm
by
5.3k points